The Dead - Hossu-Longin, Lucia (Romanian National Television, 2006)
Duration: 00:10:00 Tthe new excavations at "The Cemetary of the Poor" in Sighet - a project of investigating communist crimes initiated by the Institute for the Investigation of Communist Crimes in Romania and the Civic Adacemy Foundation